Essential and toxic trace element concentrations in different commercial veal cuts in Spain. (November 2016) - López-Alonso, M.; Miranda, M.; Benedito, J.L.; Pereira, V.; García-Vaquero, M.
Abstract: The aim of this study was to evaluate essential and toxic element concentration of ten commercially available veal cuts, together with diaphragm, cardiac muscle and liver tissue from 10 animals of "Galician Supreme Veal". Essential trace elements (Co, Cr, Cu, Fe, Mn, Mo, Ni, Se and Zn) and toxic elements (As, Cd, Hg and Pb) were determined by ICP-MS. Essential trace element concentrations ranged from 0.002–55.64 mg/kg between muscles. Toxic element concentrations were very low, and high numbers of samples showed unquantifiable residues of Cd and Pb. Veal cuts including muscles with a high proportion of oxidative slow-twitch fibers (diaphragm and cardiac muscle) showed significantly higher essential trace element concentrations, the lower concentrations being found in veal cuts including glycolytic fast-twitch fibers (eye round). Our results suggest that essential and toxic trace element concentration could be used as a new meat quality parameter, or to add further value to certain products (i.e. livestock reared on extensive systems with high physical activity). Graphical abstract: Highlights: 10 commercially available cuts of Spanish veal were evaluated. Animals showed adequate mineral status. Cuts with muscles rich in low-twitch fibers showed higher essential element accumulation. Essential and toxic trace element concentration could be used as a new meat quality parameter.